DETERMINAN KEPUASAN SISTEM PERBENDAHARAAN DAN ANGGARAN NEGARA (STUDI PADA DIREKTORAT JENDERAL PERBENDAHARAAN) - Dede Priyo Wibowo; Rosidi Rosidi; Lilik Purwanti (Jurnal Akuntansi Aktual, 2018)
One of e-government implementation in the state financial management is using of Treasury and State Budget System (SPAN) application. SPAN user satisfaction is one of the indicators that is used to measure implementation success and users acceptance. The purpose of this study is to examine the determinants of SPAN user satisfaction consisting of information quality, system quality, perceived ease of use, perceived usefulness, attitudes, intention to use and uses from Technology Acceptance Model (TAM) and DeLone and McLean model, combined with computer self efficacy and social influences. The research was conducted at Directorate General of Treasury (DJPB), Ministry of Finance, Republic of Indonesia. The study used questionnaires distributed to 432 SPAN user respondents. There were 125 questionnaires returned and successfully processed. The result of analysis with partial least square successfully showed that the whole variable is determinant of SPAN user satisfaction. The implications of this research can support the development of SPAN with attention to user satisfaction.